The Progressive Face of Contemporary Pakistani English Novel: A Study of Ali’s Night of the Golden Butterfly (2010) - Kalsoom Khan (NUML Journal of Critical Inquiry)
The present study is based in a departure from the currently abounding academic researches into contemporary Pakistani English novel exploring the cultural and religious identity crises of the local and diasporic Pakistani characters in the wake of 9/11 which constitute a single, superstructure-related segment of the aggregate social reality. The present research aims to bring to the fore a holistic and progressive strain within this corpus. Formulating a theoretical paradigm out of Marxist literary criticism as expounded in the seminal works of Leon Trotsky and K. Damodaran, the study thematically scrutinizes the narrative of Night of the Golden Butterfly (2010) by Tariq Ali for a realistic depiction of the socio-economic and political conditions of present-day Pakistan, and the delineation of the multiple spheres of life such as the economic, political, institutional, moral and intellectual as interconnected components of the composite unit of society. The study also appraises the novel for the representation of a vision for better collective future and suggestiveness in relation to the means and modes for a radical transformation of the social order.